Gender Preferences in Healthcare: A Study of Saudi Patients’ Physician Preferences - Alhomayani KM; Bukhary HA; Aljuaid FI; Alotaibi TA; Alqurashi FS; Althobaiti KN; Althobaiti NS; Althomali OY; Althobaiti AA; Aljuaid MM; Muhyei AM (Patient Preference and Adherence)
Khalid M Alhomayani,1 Hashem A Bukhary,1 Fahd I Aljuaid,1 Turki A Alotaibi,2 Faisal S Alqurashi,2 Khaled N Althobaiti,2 Nawaf S Althobaiti,2 Osama Y Althomali,2 Abdullah A Althobaiti,2 Muhanad M Aljuaid,2 Abdullah M Muhyei2 1Department of Surgery, Faculty of Medicine, Taif University, Taif, Saudi Arabia; 2Faculty of Medicine, Taif University, Taif, Saudi ArabiaCorrespondence: Khalid M Alhomayani, Department of Surgery, Faculty of Medicine, Taif University, Taif, Saudi Arabia, Tel +966502788879, Email k.homayani@tu.edu.saBackground and Objective: Cultural and social factors, including physician gender, shape patient-provider relationships in Saudi Arabia. Preferences extend beyond clinical competence to include characteristics like gender and perceived traits, potentially introducing biases. This study examines Saudi patients’ gender preferences when selecting physicians.Method: A descriptive, cross-sectional study was conducted using a survey distributed via social media from February 11 to March 23, 2024. 1. The study was conducted across various regions of Saudi Arabia, with participants recruited via social media platforms using convenience sampling aged 18 years and older who were actively pursuing medical care. A total of 3949 participants (37.9% males and 62.1% females) with a mean age of 33.43 years and a standard deviation of 19.08 were included. The response rate was 99.1%. Data analysis, including descriptive statistics and subgroup comparisons, was performed using JMP version 14 Pro.Results: The sample showed a predominance of females (62.1%) and younger participants (18– 25 years). Female participants preferred female doctors for general exams (67.9%), while males preferred male doctors (63.3%). Gender preferences were strongest for intimate examinations, with 90.8% of females and 72.3% of males favoring same-gender physicians. Similar patterns emerged in specialties like urology, where 71% of males preferred male physicians, while 64.4% of females preferred female physicians.Conclusion: Saudi patients exhibit gender preferences influenced by expertise, communication skills, and cultural norms. Gender significantly impacts comfort and satisfaction, especially in sensitive contexts like intimate exams and childbirth. These findings underscore the importance of gender-sensitive workforce planning to align physician assignments with patient preferences, enhancing satisfaction and trust. Future research should explore psychological and systemic factors driving these preferences to optimize patient-centered care and healthcare delivery systems.Keywords: physician–patient relationship, gender preferences, patient’s satisfaction, healthcare delivery, medical care preferences